The NOMA track module on nutrition human rights and governance: Part 1 Perceptions held by Master's students - M Marais; M McLachlan; W Eide (South African Medical Association, 2016)
Background. A module on nutrition, human rights and governance was developed and presented jointly by academic institutions in Norway, South Africa and Uganda, under the NOrway MAsters (NOMA) programme, for their respective Master’s degree programmes in nutrition. Consisting of three study units, it was presented consecutively in the three countries, with each study unit building on the previous one.Objectives. To document the perceptions of participating students on various aspects of the module, informing future curriculum endeavours.Methods. A mixed methods approach was followed. A module evaluation form completed by students for each study unit was analysed. In-depth telephonic interviews were voice recorded and transcribed. Through an inductive process, emerging themes were used to compile a code list and content analysis of the unstructured data.Results. An overall positive module evaluation by 20 participants (91% response rate) can be ascribed to the module content, enlightening study visits, expertise of lecturers and an interactive teaching style. Logistical issues regarding time management and administrative differences among the academic institutions caused some concerns. Students experienced some resistance against qualitative research in natural science faculties. Students benefited from being exposed to different teaching styles and education systems at universities in differentcountries. Constructive alignment of teaching and learning activities could be optimised through involvement and empowerment of all relevant lecturers.Conclusion. Successful implementation of the module not only provides nutrition Master’s students with knowledge to operationalise a human rights-based approach during future interactions in their professional practice, but also serves as an example of the benefits and challenges of interdisciplinary and transnational collaboration in module development.